Factores de riesgo asociados a la morbilidad por COVID-19 en pacientes atendidos en el Hospital Distrital el Esfuerzo de Florencia de Mora La Libertad, en el periodo enero - julio del 2021. - Lezama Lozano, Mayra Judith (2023)
In the present investigation, the risk factors associated with morbidity from COVID-19 were determined in patients treated at the Hospital Distrital el Esfuerzo de Florencia de Mora La Libertad, in the period January - July 2021. For this study, we worked with a total of 1525 epidemiological records of patients screened for COVID-19; for which authorization was requested for access to the information, the correctly filled out records and database with complete information were selected, and finally the records of patients who met the risk factors during the study period. The data obtained were processed in the statistical package SPSS Ver 25, to establish the relationship between the study variables, the Chi Square test was applied, using a confidence level of 95%. It was found that the risk factors associated with morbidity from COVID-19 were obesity, diabetes, cardiovascular disease, over 60 years of age, HIV, tuberculosis, asthma, cancer, lung disease, and arterial hypertension. Finding a significant relationship between the factors obesity, diabetes, cardiovascular disease and over 60 years with morbidity from COVID-19. According to gender, it can be seen that 18.6% of female patients were positive for the diagnosis of COVID-19, while 15.1% of male patients only tested positive for this diagnosis. According to age group, the highest percentage of patients diagnosed with COVID-19 are in the age group between 41 to 50 years, followed by the group 21 to 30 years. The behavior of the risk factors associated with morbidity from COVID-19 was evaluated according to the gender and age of the patients